Membangun Citra Perpustakaan Perguruan Tinggi - Panti Astuti (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2016)
Improved image of medium scale, we can see from some of the college library ranging from the construction of the library website up to reorganize the collection and the room. In the era of the 1980s and 1990s the concept of a library is considered taboo or even not allowed any food or drink in the library because it can bring in the rat, which can damage the collection. Currently there have also been merging a library room with a home theater, so it went into the library building can be treated to interesting movies, and so forth. Image enhancement college library as a professional institution in providing information services to the campus community will open up the minds of their (campus community) that the library can be used as an alternate means of independent learning. Some management approach is used as a strategy to improve the image library. Strategy three pillars of the main image presented above, provide an alternative thinking to develop the library into a modern information center and professional.